The Superiority of the Time-to-Event Continual Reassessment Method to the Rolling Six Design in Pediatric Oncology Phase I Trials - Zhao, Lili (Clin Trials, 2011)
BACKGROUND: The Rolling Six Design (RSD) is currently being used by the Children’s Oncology Group (COG) as their standard design for Phase I trials. Because the COG has large multi-center trials with fast accrual, the motivation for adopting the RSD is to hasten accrual and shorten the duration of their trials. However, trial suspension due to completion of follow-up still cannot be entirely avoided by the RSD. Therefore, a design that allows continuous enrollment of patients throughout the entire trial is needed. PURPOSE: To demonstrate the superior performance of the Time-to-Event Continual Reassessment Method (TITE-CRM) with continuous patient recruitment relative to the RSD, in terms of identifying the maximum tolerated dose (MTD) and reducing exposure of patients to toxic doses. METHODS: Using scenarios that were based on an actual pediatric Phase I trial at the University of Michigan, Monte Carlo simulations were used to investigate the operational characteristics of RSD and TITE-CRM. RESULTS: The TITE-CRM treated all available patients, identified the MTD more accurately than the RSD and did not increase the probability of exposing patients to toxic doses. LIMITATIONS: Both the TITE-CRM and RSD assume that the probability of dose limiting toxicity increases with higher dose level. CONCLUSIONS: The TITE-CRM, which allows for continual enrollment of patients, provides a safe design for pediatric oncology Phase I trials with better accuracy than the RSD.